2020
DOI: 10.1080/10717544.2020.1716879
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel, DNA binding heterocyclic dehydroabietylamine derivatives as potential antiproliferative and apoptosis-inducing agents

Abstract: Several dehydroabietylamine derivatives containing heterocyclic moieties such as thiophene and pyrazine ring were successfully synthesized. The antiproliferative activities of these thiophene-based Schiffbases, thiophene amides, and pyrazine amides were investigated in vitro against Hela (cervix), MCF-7 (breast), A549 (lung), HepG2 (liver), and HUVEC (umbilical vein) cells by MTT assay. The toxicity of L 1 ÀL 10 (IC 50 ¼ 5.92À >100 lM) was lower than L 0 (1.27 lM) and DOX (4.40 lM) in every case. Compound L 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…ROS can represent a new standard for determining cytotoxicity because increasing intracellular ROS interferes with the oxidative environment of cells and induces cell death [ 32 ]. In vivo experiments have indicated that anthocyanins can prevent and treat cancer, with the relative tumor proliferation rate (T/C) being 44.67% and the tumor inhibition rate being 52.76%, similar to our previous paper covering the anticancer activity of natural products and suggesting that it has excellent antiproliferative effects [ 29 , 35 ]. The further mechanism might be that S 1 can induce apoptosis by interacting with DNA in an intercalation mode, changing or destroying DNA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…ROS can represent a new standard for determining cytotoxicity because increasing intracellular ROS interferes with the oxidative environment of cells and induces cell death [ 32 ]. In vivo experiments have indicated that anthocyanins can prevent and treat cancer, with the relative tumor proliferation rate (T/C) being 44.67% and the tumor inhibition rate being 52.76%, similar to our previous paper covering the anticancer activity of natural products and suggesting that it has excellent antiproliferative effects [ 29 , 35 ]. The further mechanism might be that S 1 can induce apoptosis by interacting with DNA in an intercalation mode, changing or destroying DNA.…”
Section: Discussionsupporting
confidence: 81%
“…However, after adding DNA, the fluorescence intensity significantly increased due to the strong insertion of DNA base pairs. The compound’s intercalation into the DNA base pair was confirmed when fDNA-EB emission was reduced or quenched after adding the compound [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…After adding DNA, the fluorescence intensity improved, which was considered to be due to its strong intercalation with DNA base pairs. The intercalation of the compound with the base pairs of DNA was confirmed when the fDNA-EB emissions were decreased or quenched upon adding a compound [ 41 , 42 , 43 ]. As expected, the emission intensity reduced (shown in Figure 7 ) by adding L 1 to fDNA-EB, which showed that L 1 can bind to DNA at the sites occupied by EB and that it can interact with DNA via intercalation.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability values were determined (at least three times) according to the following equation: cell viability (%) = the absorbance of the experimental group/the absorbance of the blank control group × 100%. [35][36][37] Induction of apoptosis by flow cytometric analysis in vitro. Induction apoptosis assay was performed using a Becton Dickinson Ultra-high speed separation flow cytometry instrument and Annexin V-FITC/PI was purchased from Beyotime Biotechnology Co. Ltd.…”
Section: Biological Experimentsmentioning
confidence: 99%